Edward Zigler's legacy in the study of persons with intellectual disability: the developmental approach and the advent of a more rigorous and compassionate science. Issue 1 (10th December 2019) - Burack, J. A.; Evans, D. W.; Lai, J.; Russo, N.; Landry, O.; Kovshoff, H.; Goldman, K. J.; Iarocci, G.
Abstract: Edward Zigler transformed the science and humanity of the work with persons with intellectual disability. The developmental approach is Ed's great contribution to the field of intellectual disability as it both led to more conceptually compelling and methodologically rigorous science and provided an alternative to the Zeitgeist of segregation, defect, and pathology that had prevailed for decades. In an entirely unique way, the developmental approach allowed a seamless integration of increasingly precise science with concern for the "whole child" and their family. Thus, Ed's legacy led to a discipline in which scholarship and compassion prevail hand in hand as the integrity of science and of the person are mutually informative and interdependent.